Limbal epithelial stem cell activity and corneal epithelial cell cycle parameters in adult and aging mice - Sagga, Nada (Stem Cell Res, 2018)
Limbal epithelial stem cells (LESCs) are believed to be responsible for corneal epithelial maintenance and repair after injury, but their activity has never been properly quantified in aging or wounded eyes. In this study, labelling with thymidine analogues, 5-iodo-2′-deoxyuridine (IdU), 5-chloro-2′-deoxyuridine (CldU) and 5-ethynyl-2′-deoxyuridine (EdU), was used to estimate cell-cycle time of the corneal and limbal epithelia in wild-type eyes, comparing aging (12 months) and young adult (8 week) mice. In C57BL/6 mice, cells cycled significantly faster in the central corneal epithelium of aging eyes (3.24 ± 0.2 days) compared to 10 week old mice (4.97 ± 0.5 days). Long-term labelling with IdU was used to detect slow-cycling stem cells, followed by CldU or EdU labelling to quantify the proliferative dynamics of LESCs during corneal wound healing. In unwounded eyes, 4.52 ± 1.4% of LESCs were shown to enter S phase in a 24 h period and were estimated to divide every 2–3 weeks. Within 24 h of corneal injury this rose significantly to 32.8 ± 10.0% of stem cells indicating a seven-fold increase in activation. In contrast, no comparable increase in LESC activation was observed in aging mice after wounding. In the 24–48 h period after wounding in young adults, LESC activation continued to increase (86.5 ± 8.2% of label-retaining cells in wounded eye were in S-phase) but surprisingly, 46.0 ± 9.4% of LESCs were observed to reenter S-phase in the contralateral unwounded eye. These data imply an unsuspected systemic effect of corneal wounding on LESC activation suggesting that injury to one eye elicits a regenerative response in both.